Experimental investigation of the biaxial strength of thermal barrier coating system. Issue 7 (August 2015) - Su, Luochuan; Zhang, Weixu; Chen, Xi; Wang, T.J.
Abstract: A piston-on-three-ball assembly is employed to evaluate the biaxial strength of the ceramic top-coat in thermal barrier coating system (TBCs). The design of bi-axial experiment is presented, in which the effects of the specimen geometric parameters, the contact between the specimen and the support, and the plastic deformation of substrate are numerically analyzed. Then, the piston-on-three-ball tests and Scanning Electron Microscopy (SEM) observations are carried out to measure the bi-axial strength and the failure patterns of the ceramic top-coat in TBCs, respectively. We experimentally obtained the bi-axial fracture strength of the ceramic top-coat in thermal barrier coating system, which obeys Weibull distribution function. The fracture patterns of the ceramic top-coat under bi-axial loading exhibit a typical channel network.